The new Africans: a textual analysis of the construction of 'African-ness' in Chaz Maviyane-Davies' 1996 poster depictions of the Universal Declaration of Human Rights - Garman, Brian Donald (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2013)
In 1996, Zimbabwean graphic designer Chaz Maviyane-Davies created a set of human rights posters which represent several articles of the Universal Declaration of Human Rights, from what he calls an "African perspective" . In this study I investigate how Maviyane-Davies has constructed 'African-ness' and probe what he refers to as the "alternative aesthetic" that he is trying to create. I use a visual social semiotic approach to examine the discourses he draws on to re-image and re-imagine Africa and Africans in a manner that contests the stereotypical representations found in political, news and economic discourses about Africa, paying particular attention to the ways he uses images of the body. My analysis of the posters shows how complex and difficult it can be to contest regimes of representation that work to fix racialised and derogatory meanings. In response to the pejorative stereotypes of the black body, Maviyane-Davies uses images of strong, healthy, and magnificent people (mostly men) to construct a more affirmative representation of Africa and Africans. Significantly, he draws on sports, touristic, traditional and hegemonic discourses of masculinity in an attempt to expand the complexity and range of possible representations of African-ness. In so doing he runs the risk of reproducing many of the stereotypes that sustain not only the racialised and gendered (masculinist) representations of Africa, but also a sentimentalisation and romanticisation of a place, a people and their traditions. Apart from women in prominent positions, other conspicuous absences from these images include white people and hegemonic references to Western modernity. I do not believe he is discarding whites and modernity as un-African, but is rejecting the naturalisation of whiteness as standing in for humanity, and particular icons of Western modernity as significations of 'modernity' itself
Keywords: Human rights; Posters; African perspective; Stereotypes; Black men; Maviyane-Davies, Chaz -- Criticism and interpretation; Universal Declaration of Human Rights -- Posters -- Research; Ethnicity -- Research -- Africa; Human rights -- Africa; Pan-Africanism